PENGARUH LOKASI DAN BRAND IMAGE SERTA KUALITAS LAYANAN TERHADAP KEPUASAN PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS JEMBER - Irmawati, Herliana; Yulisetiarini, Diah; Wulandari, Deasy (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: The purpose of this study was to examine the effect of location, brand image, and service quality on student satisfaction in Universitas Jember. This was an explanatory research. Data were collected in December 2016. The study population was undergraduate students in the Faculty of Medicines, Universitas Jember. The Faculty of Medicines was selected because it had the largest number of registrants while the quota for the accepted students was very limited. The total number of the Faculty of Medicines’ students in 2015/2016 was 85 (eighty five). The sample consisted of 96 (ninety six) respondents because all undergraduate students batch 2015/2016 were used as the sample. Data were analyzed using multiple linear regression. Keywords: Location, Brand Image, Service Quality, and Satisfaction